(untitled) (Fiep Bulletin - online, 2015)
Nowadays Quality of Life (QL) has been the focus of several researches and now more than ever the professionals in the Healthcare area worry about it. This study aims at analyzing the QL of individuals from two Brazilian Army Barracks, as well as to establish a relation between QL and physical fitness concerning health. The sample was composed of 65 male individuals serving the Army Barracks settled in Lapa-Pr (n=37) and Ponta Grossa-Pr (n=28) cities and the average age ranging from 18 and 28. The QL was measured through the (WHOQOL-Bref) and the corporal composition, the cardio respiratory aptitude and the upper limbs strength were considered in the evaluation of physical fitness. The criteria proposed by the Australian team of WHOQOL were used in the analysis of the questionnaire on QL. Kendall’s correlation coefficient test was used to correlate the physical fitness with the physical domain of WHOQOL-Bref intra group. The Mann-Whitney test was administered to analyze the differences in answers to the WHOQOL-Bref questionnaire between the two groups. The general results of QL were satisfactory for both groups, and the environmental domain obtained the lowest percentage values in the two groups. Kendall’s correlation coefficient test showed a relation between the Physical Domain and the variables % of fat and strength for Ponta Grossa-Pr (n=28) city sample, and between the Physical Domain and the variables IMC, strength and Vo2max for Lapa-Pr city sample. The Mann-Whitney test analysis showed a significant difference (p=0,049) between the quality of life of the two groups, with the individuals from Ponta Grossa-Pr city surpassing the individuals from Lapa-Pr city. Taking into account the limitations of this study, it can be stated that the physical fitness analyzed may present some relation with the WHOQOL physical domain and consequently with the overall QL.